-60y+2y-5*3=5(2y-57)*30-5*10

Simple and best practice solution for -60y+2y-5*3=5(2y-57)*30-5*10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -60y+2y-5*3=5(2y-57)*30-5*10 equation:



-60y+2y-5*3=5(2y-57)*30-5*10
We move all terms to the left:
-60y+2y-5*3-(5(2y-57)*30-5*10)=0
We add all the numbers together, and all the variables
-58y-(5(2y-57)*30-5*10)-15=0
We calculate terms in parentheses: -(5(2y-57)*30-5*10), so:
5(2y-57)*30-5*10
We add all the numbers together, and all the variables
5(2y-57)*30-50
We multiply parentheses
300y-8550-50
We add all the numbers together, and all the variables
300y-8600
Back to the equation:
-(300y-8600)
We get rid of parentheses
-58y-300y+8600-15=0
We add all the numbers together, and all the variables
-358y+8585=0
We move all terms containing y to the left, all other terms to the right
-358y=-8585
y=-8585/-358
y=23+351/358

See similar equations:

| 12w–9w=3 | | x=22+(1/2)x | | _h7.8=2__ | | 6+u=2 | | 5n-8n=-32 | | 48x=6⋅12 | | 35=2(x+61) | | 3n+3=2n=8 | | 129= | | -15a=17 | | 7(x-2)+3(x+2)=(5x-6) | | 3r^2-4r-1=0 | | 5=u/2-12 | | 5x+5=4x+22 | | 3r-7+9r=30 | | k2-4k+1=-5 | | -9=-6r | | 10x=-34 | | 8x+12=x+6 | | 5(4x-2)+x+2=-34 | | 6x-4=12x+11 | | -6n=-8 | | -1y+8=37y | | 3√a+4=4 | | 6=​8​​m | | 6*(x+12)= | | 6⋅(x+12)= | | 5(-2x-4)-5x+5=-15 | | ^3√a+4=4 | | 7x+2=10x-10 | | 3(x+5)=11.85 | | 4(w+6)=-6w+4 |

Equations solver categories